Ghana : Poverty Reduction Strategy Paper; Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2009)
This Joint Staff Advisory Note provides IMF staff advice on key priorities for strengthening the Growth and Poverty Reduction Strategy (GPRS II) for Ghana and for ensuring its effective implementation. It highlights critical areas that could justify renewed focus. IMF staff commends the Ghanaian authorities for the breadth and scope of the document, as well as the candid treatment of some of the issues. IMF staff also welcomes the progress in several areas reported in the annual progress report.